2014
DOI: 10.1177/0363546514561435
|View full text |Cite
|
Sign up to set email alerts
|

MRI Volume and Signal Intensity of ACL Graft Predict Clinical, Functional, and Patient-Oriented Outcome Measures After ACL Reconstruction

Abstract: Background Clinical, functional and patient-oriented outcomes are commonly used to evaluate the efficacy of treatments following ACL injury; however, these evaluation techniques do not directly measure the biomechanical changes that occur with healing. Purpose To determine if the magnetic resonance (MR) image-derived parameters of graft volume and signal intensity (SI), which have been used to predict the biomechanical (i.e., structural properties) of the graft in animal models, correlate with commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 32 publications
1
117
0
Order By: Relevance
“…This should not be neglected, as lack of incorporation of the graft and biological failure are wellrecognised causes of poor outcomes after ACL reconstruction (3). Moreover, graft healing, measured by graft signal intensity on magnetic resonance imaging (MRI), has been shown to affect anteroposterior (AP) laxity and clinical or functional outcomes (4). Therefore, the clinician should be aware that graft maturation is a slow process that can even take longer than two years (5,6), and must be sure that it is complete before allowing activities that could stress an incompletely remodelled graft.…”
Section: Genetics/biological Responsementioning
confidence: 99%
“…This should not be neglected, as lack of incorporation of the graft and biological failure are wellrecognised causes of poor outcomes after ACL reconstruction (3). Moreover, graft healing, measured by graft signal intensity on magnetic resonance imaging (MRI), has been shown to affect anteroposterior (AP) laxity and clinical or functional outcomes (4). Therefore, the clinician should be aware that graft maturation is a slow process that can even take longer than two years (5,6), and must be sure that it is complete before allowing activities that could stress an incompletely remodelled graft.…”
Section: Genetics/biological Responsementioning
confidence: 99%
“…In Press(In Press):e14060. 5 U n c o r r e c t e d P r o o f the entire course of the graft has been studied and it was shown that IGSI is a dynamic process of healing and by 2-years postreconstruction, the graft should resume uniformly low GSI on MRI (18,19 (2,20). In our study, IGSI of the IAP was observed in 36.6 %, and only 9.8% of patients showed low GSI of the entire graft course.…”
Section: Discussionmentioning
confidence: 47%
“…GSI in the early postreconstruction period has been well studied, however few studies evaluated the GSI at midor long-term follow-up (2,4,17). In short-term studies, Iran J Radiol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations